Comparaison between dry and wet anaerobic fermentation process of dairy cattle manure under different temperatures (Journal of Hama University, 2022)
The anaerobic batch fermentation of undiluted (dry) dairy cattle manure under psychrophilic, mesophilic and thermophilic conditions was studied to establish its biodegradability and compare the feasibility with conventional process (diluted manure). The biodegradability of undiluted manure was 0.5%, 11.5%, 30.7%, 44.9% and 1.1% as compared with 0.4%, 10.2%, 32.5%, 53.1% and 32.4% observed for the diluted manare at 15°C, 25°C, 35°C, 45°C and 55°C temperatures, respectively. The low biodegradability    (P